2022
DOI: 10.3390/pr10102026
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Rice Bran Protein (RBP) Powder Using Spray Drying Method at the Optimal Condition and Its Protein Quality

Abstract: Rice bran is a by-product of the rice milling process. It contains a high concentration of protein. Rice brans are frequently utilized as feed cattle, fertilizer, and fuel. However, their application as human nutrition supplements is uncommon, and the necessary process for this purpose is yet to be established, including the drying process. This study aims to evaluate the effect of the spray-drying parameters, the inlet temperature, inlet flowrate, and inlet air flowrate, on rice bran protein (RBP) powder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…However, the success of the drying process will later be determined by the revival and growth ability of the powder culture. Similar results were obtained by Mansor et al as they found that at low temperature, the particle size was higher due to the low evaporation process [19]. Low evaporation will cause high-density membranes, high water content, poor fluidity, and agglomeration of the particles.…”
Section: Effect Of Inlet Temperature On Yield Percentage Of Fruiting ...supporting
confidence: 86%
“…However, the success of the drying process will later be determined by the revival and growth ability of the powder culture. Similar results were obtained by Mansor et al as they found that at low temperature, the particle size was higher due to the low evaporation process [19]. Low evaporation will cause high-density membranes, high water content, poor fluidity, and agglomeration of the particles.…”
Section: Effect Of Inlet Temperature On Yield Percentage Of Fruiting ...supporting
confidence: 86%
“…Rice bran was procured from Kilang Beras BERNAS Sdn Bhd in Kuala Perlis, Perlis. To inhibit hydrolytic rancidity, the unprocessed rice bran underwent a 3-minute heating process, following the method described by Mansor et al, [19]. Subsequently, it was kept at a temperature of 4˚C until the commencement of the experimental process.…”
Section: Methodology 21 Materials Preparationmentioning
confidence: 99%

A Three-Level Factorial Model for Maximising Protein Extraction from Rice Bran with Choline Chloride: Glycerol

Kamalea Amaleena Farhana Kamal Ramlee,
Nik Muhammad Azhar Nik Daud,
Mohd Sharizan Md Sarip
et al. 2024
ARMNE